2013
DOI: 10.1177/0892020612471698
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities of the collaborative mentoring relationships between teachers and student teachers in the classroom

Abstract: This article explores the views of teachers, student teachers and university tutors about the opportunities of the collaborative mentoring relationships between teachers and student teachers. A qualitative approach was employed to conduct the study using a semi-structured type of interview with teachers, student teachers and university tutors. Data collected were analysed thematically and discussed. Findings indicate that the collaborative mentoring relationships provide opportunities for learning from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Despite this evidence, it is also believed that as learning is individualistic, good teachers can work individually to achieve education goals. This perhaps, justifies the argument that mentoring should be studied constantly within specific contexts (Aderibigbe, 2013). Against this backdrop, this article addresses the following research question:…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Despite this evidence, it is also believed that as learning is individualistic, good teachers can work individually to achieve education goals. This perhaps, justifies the argument that mentoring should be studied constantly within specific contexts (Aderibigbe, 2013). Against this backdrop, this article addresses the following research question:…”
Section: Introductionmentioning
confidence: 79%
“…Much has been documented about mentoring students on TP in extant literature (Aderibigbe, 2013;Kaasila & Lauriala, 2010;Leshem, 2012). However, this literature is seemingly dominated by a focus on mentors and students' experiences in isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature indicates mentoring fosters the professional development of student teachers, early career teachers, and experienced teachers (Aderibigbe, 2013;Aspfors & Bondas, 2013;Kutsyuruba, 2012). It is also reported that mentoring between teachers and student teachers underpinned by collaborative philosophy aids students' learning (Aderibigbe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates mentoring fosters the professional development of student teachers, early career teachers, and experienced teachers (Aderibigbe, 2013;Aspfors & Bondas, 2013;Kutsyuruba, 2012). It is also reported that mentoring between teachers and student teachers underpinned by collaborative philosophy aids students' learning (Aderibigbe, 2013). Not surprisingly, collaborative endeavors between teachers and student teachers are seen as an integral component of effective teacher education (Blase´, 2009;Hudson, 2013;Nevin, Thousand, & Villa, 2009).…”
Section: Introductionmentioning
confidence: 99%